2017
DOI: 10.5114/wiitm.2017.68895
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and safety of thoracoscopic surgery under epidural and/or local anesthesia for spontaneous pneumothorax: a meta-analysis.

Abstract: The aim of this study was to compare thoracoscopic surgery for spontaneous pneumothorax under epidural and/or local anesthesia (ELA) with that under general anesthesia and prove the feasibility and safety of thoracoscopic surgery under ELA for spontaneous pneumothorax. Relevant studies were searched in five databases from their date of publication to June 2016. We collected and analyzed the data concerning operative time, hospital stay, complications, air leak, recurrence and perioperative mortality. A forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The mean was 66 minutes in the non-intubated group, and 78 minutes in the intubated group, which was considered statistically significant [ 17 ]. In the meta-analysis of Chen et al , although there are similarities among the patients, it was reported that the time spent in the operations room was shortened, and side effects related to general anaesthesia were not observed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean was 66 minutes in the non-intubated group, and 78 minutes in the intubated group, which was considered statistically significant [ 17 ]. In the meta-analysis of Chen et al , although there are similarities among the patients, it was reported that the time spent in the operations room was shortened, and side effects related to general anaesthesia were not observed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%